Design of fiber bragg grating (FBG) temperature sensor based on optical frequency domain reflectometer (OFDR) - Nani Fadzlina Naim; Siti Noor Maslizan Sudin; Suzi Seroja Sarnin; Norsuzila Ya'acob; Latifah Sarah Supian (Institute of Advanced Engineering and Science, 2020)
In this paper, the simulation of Fiber Bragg Grating (FBG) as a temperature sensor is conducted. The FBG temperature sensor is designed based on Optical Frequency Domain Reflectometer (OFDR) concept. A continuous wave (CW) laser is used as the optical source and it is transmitted to two FBGs. The two FBGs reflection spectra will produce a beat frequency that can be detected using a Radio Frequency (RF) Spectrum Analyzer. Any temperature change will shift Bragg wavelength, thus produce a shift for the beat frequency. In this work, an FBG with temperature sensitivity 10 pm/˚C is employed. It is found that by using this technique, a high-resolution temperature sensor can be designed with temperature resolution of 0.1˚C.